Enhancing the experience of food and drink via neuroscience-inspired olfactory design - Spence, C (Taylor and Francis, 2017)
Olfactory cues, both orthonasal (when we inhale) and retronasal (when we swallow/breathe out from the back of the nose), play a crucial role in the experience, and enjoyment, of food and drink. However, the design of product packaging glassware, and even plateware has typically not been optimized to deliver the ideal orthonasal hit. This review highlights a number of recent attempts by packaging manufacturers to improve the orthonasal experience for the consumer. The various ways in which modernist chefs, molecular mixologists, culinary artists, and designers have been playing with the delivery of both foreground and background aromas and scents in order to complement the dishes and drinks they serve is also examined. Finally, I highlight some of the ways that technology may be used to deliver food aromas in the future, and stress the need for more research in order to determine whether enhanced olfactory design (e.g., in scent-enabled cutlery and packaging) may one day be used to help nudge consumers toward healthier eating behaviours. The important distinction between natural and synthetic (or better said, between perceived natural vs. perceived synthetic) aromas is also discussed, as this will likely play an important role in determining the future uptake of such innovative olfactory delivery solutions in the future.